The prevalence of pelvic organ prolapse symptoms and signs and their relation with bladder and bowel disorders in a general female population - Slieker-ten Hove, Marijke C. Ph. (Springer-Verlag, 2009)
INTRODUCTION AND HYPOTHESIS: In selected populations, pelvic organ prolapse (POP) was associated with bladder/bowel symptoms, but data on the general female population are lacking. Our aim was to obtain normative data on the prevalence of POP and pelvic floor dysfunction (PFD) symptoms and signs and to identify associations. METHODS: Validated questionnaires on POP and PFD (urogenital distress inventory, (UDI) and defaecation distress inventory (DDI)) were sent to a general population of 2,979 women (aged 45–85 years). Data were analysed using the Kruskal–Wallis test, chi square test and Spearman’s rank correlation coefficient. RESULTS: Response rate was 62.7%. Associations between POP stage and parity (0.002) and vaginal bulging (<0.001) are significant. Anatomical locations of POP and PFD symptoms correlated significantly with incontinence of flatus, feeling anal prolapse, manual evacuation of stool, vaginal bulging, constipation and pain during faecal urge (p ≤ 0.005). CONCLUSIONS: Strategies should be developed to alleviate obstructive bowel disorders associated with POP.